The Optimized Calculation Method for Insulin Dosage in an Insulin Tolerance Test (ITT): A Randomized Parallel Control Study - Zhang, Yuwen; Sun, Shouyue; Jia, Huiying; Qi, Yan; Zhang, Jie; Lin, Lin; Chen, Yuhong; Wang, Weiqing; Ning, Guang (Frontiers in Endocrinology, 2020)
Objective: To explore the most suitable calculation method for insulin dosage in an insulin tolerance test (ITT) and to evaluate the clinical application value of the optimization coefficient (γ). Methods: In this study, 140 adult patients with congenital growth hormone deficiency (GHD) or acquired hypopituitarism were randomized into the following two groups: the conventional group (n = 70) and the optimized group (n = 70). Oral glucose tolerance tests (OGTTs), insulin release tests (IRTs), and ITTs were conducted. For ITTs, insulin doses were the product of body weight (kg) and related coefficient (0.15 IU/kg for the control group and γ IU/kg for the optimized group, respectively). Notably, γ was defined as − 0.034 + 0.000176×AUCINS + 0.009846×BMI, which was based on our previous study. Results: In the ITTs, the rate of achieving adequate hypoglycemia with a single insulin dose was significantly higher for the optimized group compared with the conventional group (92.9% vs 60.0%, P < 0.001). The optimized group required higher initial doses of insulin (0.23 IU/kg). Meanwhile, the two groups did not differ significantly in their nadir blood glucose (1.9 vs 1.9 mmol/L, P = 0.828). Conclusion: This study confirmed that the proposed optimized calculation method for insulin dosage in ITTs led to more efficient hypoglycemia achievement, without increasing the incidence of serious adverse events.